Effectiveness of Aerodrome Controller Refresher Training To Maintain Competency of Aerodrome Controllers - Agung Ayu Mas Oka, I Gusti; Komalasari, Yeti; Badeni, Badeni (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The training effectiveness is an assessment of degree to which training can enhance knowledge, skills, and attitudes of participants in alignment with the training objectives. Furthermore, assessing training effectiveness also encompassed evaluating the training program itself. The aim of this study is to investigate effectiveness of Aerodrome Controller Refresher Training in order to maintain competency of Aerodrome Controllers. CIPRL (context, input, process, reaction, and learning) was an evaluation model used in this study. Variables assessed in the context were policies and training objectives. Variables assessed in the input were training materials and training facilities. Variable assessed in the process was the training process, consists of training preparation, implementation, and evaluation. Variable assessed in the reaction was the satisfaction of training participants. Finally, variable assessed in the learning was the score of the training participants. The results of this study were indicated that all variables investigated align with established standards, leading to conclusion that the training has been carried out effectively and has successfully met the goal. To maintain the competency of aerodrome controllers was the primary goal of this training. Some recommendations were provided to enhance the effectiveness of Aerodrome Controllers Training.